Pengaruh Struktur Aktiva Dan Likuiditas Terhadap Struktur Modal Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Manufaktur (Sektor Industri Barang Konsumen Primer) Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023 - Nurhajjah, Afifah; Lusiana, Lusiana; Sari, Yosi Puspita (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This study aims to determine the effect of Asset Structure and Liquidity on Capital Structure with Profitability as an Intervening Variable. The population used in this study is the (primary consumer goods industrial sector) manufacturing companies listed on the Indonesia Stock Exchange (IDX) year 2019-2023. The sampling technique used is purposive sampling and 30 companies were obtained as samples with 150 observations. The analysis method used is multiple linear regression analysis. The results of the study in equation 1 show that the asset structure affects profitability. While liquidity does not affect profitability. And for the results of the study from equation 2 liquidity and profitability affect the capital structure. While the asset structure does not affect the capital structure. For the profitability variable, it cannot mediate the effect of asset structure on capital structure. While the profitability variable can mediate the effect of liquidity on capital structure in primary consumer goods manufacturing companies listed on the Indonesia Stock Exchange in 2019-2023.